Desmoplastic Adamantinoma-like Thymic Carcinoma: Clinicopathologic, Immunohistochemical, and Molecular Study of 5 Cases. (22nd December 2022) - Suster, David I.; Mejbel, Haider; Mackinnon, Alexander C.; Suster, Saul
Abstract : Five cases of a heretofore unreported rare variant of thymic carcinoma characterized by a striking resemblance to adamantinoma of the mandible are described. The tumors occurred in 4 women and 1 man aged 58 to 76 years (mean: 67.8 y); they arose in the anterior mediastinum and measured from 5.3 to 12.0 cm in greatest diameter (mean: 8.9 cm). Presenting symptoms included chest pain, shortness of breath, and in 2 patients, pleural effusion. One tumor was asymptomatic and discovered incidentally. Histologically, the tumors were extensively desmoplastic, and the cellular proliferation was characterized by multiple islands of squamous epithelium with striking peripheral palisading of nuclei and central areas containing clear cells resembling a stellate reticulum. Areas of preexisting spindle cell thymoma were identified in 2 cases; these areas gradually merged with the higher-grade component of the lesion. Cystic changes were noted in 3 cases. Immunohistochemical studies in 3 cases showed the tumor cells were positive for cytokeratins, p40 and p63, and all showed a high proliferation rate (>50% nuclear positivity) with Ki-67. Next-generation sequencing was performed in 2 cases that showed amplification of the AKT1 gene (copy numbers 6 and 13). Clinical follow-up in 3 patients showed recurrence and metastasis after 1 and 2 years; 1 patient passed away 2 years after diagnosis due to the tumor. Desmoplastic adamantinoma-like thymic carcinoma represents an unusual histologic variant of thymic carcinoma that needs to be distinguished from metastases from similar tumors to the mediastinum.